Comparison of some cardiopulmonary effects of etorphine and thiafentanil during the chemical immobilization of blesbok (Damaliscus pygargus phillipsi). (January 2021) - Pfitzer, Silke; Meyer, Leith; Laubscher, Liesel; Warren, Kristin; Vaughan-Higgins, Rebecca; Raath, Jacobus P.; Laurence, Michael
Abstract: Objective: To determine the cardiopulmonary effects of etorphine and thiafentanil for immobilization of blesbok. Study design: Blinded, randomized, two-way crossover study. Animals: A group of eight adult female blesbok. Methods: Animals were immobilized twice, once with etorphine (0.09 mg kg –1 ) and once with thiafentanil (0.09 mg kg –1 ) administered intramuscularly by dart. Immobilization quality was assessed and analysed by Wilcoxon signed-rank test. Time to final recumbency was compared between treatments by one-way analysis of variance. Cardiopulmonary effects including respiratory rate (ƒR ), arterial blood pressures and arterial blood gases were measured. A linear mixed model was used to assess the effects of drug treatments over the 40 minute immobilization period. Significant differences between treatments, for treatment over time as well as effect of treatment by time on the variables, were analysed ( p < 0.05). Results: There was no statistical difference ( p = 0.186) between treatments for time to recumbency. The mean ƒR was lower with etorphine (14 breaths minute –1 ) than with thiafentanil (19 breaths minute –1, p = 0.034). The overall mean PaCO2 was higher with etorphine [45 mmHg (6.0 kPa)] than with thiafentanil [41 mmHg (5.5 kPa), p = 0.025], whereas PaO2 was lower with etorphine [53 mmHg (7.1 kPa)] than with thiafentanil [64 mmHg (8.5 kPa), p < 0.001]. The systolic arterial pressure measured throughout all time points was higher with thiafentanil than with etorphine ( p = 0.04). The difference varied from 30 mmHg at 20 minutes after recumbency to 14 mmHg (standard error difference 2.7 mmHg) at 40 minutes after recumbency. Mean and diastolic arterial pressures were significantly higher with thiafentanil at 20 and 25 minute measurement points only ( p < 0.001). Conclusions: Both drugs caused clinically relevant hypoxaemia; however, it was less severe with thiafentanil. Ventilation was adequate. Hypertension was greater and immobilization scores were lower with thiafentanil.